Critical Perspectives on Open Development Empirical Interrogation of Theory Construction - Chib, Arul; Bentley, Caitlin M.; Smith, Matthew L. (The MIT Press, 2020)
Cross-cutting theoretical frameworks and analyses examine how open innovations in international development can empower poor and marginalized populations. Over the last ten years, "open" innovations-the sharing of information and communications resources without access restrictions or cost-have emerged within international development. But do these innovations empower poor and marginalized populations? This book examines whether, for whom, and under what circumstances the free, networked, public sharing of information and communication resources contribute (or not) toward a process of positive social transformation. The contributors offer cross-cutting theoretical frameworks and empirical analyses that cover a broad range of applications, emphasizing the underlying aspects of open innovations that are shared across contexts and domains. The book first outlines theoretical frameworks that span knowledge stewardship, trust, situated learning, identity, participation, and power decentralization. It then investigates these frameworks across a range of institutional and country contexts, considering each in terms of the key emancipatory principles and structural impediments it seeks to address. Taken together, the chapters offer an empirically tested theoretical direction for the field. Contributors Juan Pablo Alperin, Caitlin M. Bentley, Bidisha Chaudhuri, Nandini Chami, Arul Chib, Purnabha Dasgupta, Andy Dearden, Melissa Densmore, Helani Galpaya, Piyumi Gamage, Anita Gurumurthy, Onkar Hoysala, Linus Kendall, Rich Ling, Goodiel Moshi, Chiranthi Rajapakse, Katherine Reilly, Paul Mungai, Priya Parekh, Chiranthi Rajapakse, Anuradha Rao, Katherine Reilly, David Sadoway, Deo Shao, Parminder Jeet Singh, Matthew L. Smith, Janaki Srinivasan, Bernd Carsten Stahl, Satyarupa Shekhar Swain, John Traxler, Jean-Paul Van Belle, Marion Walton, Yingqin Zheng